IMPLIKASI PENDIDIKAN YANG BERPUSAT PADA KRISTUS DALAM KELAS MATEMATIKA [THE IMPLICATIONS OF CHRIST-CENTER EDUCATION FOR MATHEMATICS CLASSES] - Saragih, Melda Jaya; Hidayat, Dylmoon; Tamba, Kimura Patar (Universitas Pelita Harapan, 2019)
The purpose of education is to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. But in practice, much education separates science and faith in God. Christian education allows students to get to know God more and develops the potential of each student according to God's truth and purpose. Mathematics learning should be a tool to bring students to see and admire God as the great Creator. Investigation and discovery in learning mathematics should acknowledge some of God's attributes and allow students to admire the beauty of mathematics and to praise God.BAHASA INDONESIA ABSTRACT: Tujuan pendidikan adalah untuk mengembangkan potensi peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab. Namun pada pelaksanaannya, banyak pendidikan memisahkan ilmu pengetahuan dan iman kepada Tuhan. Pendidikan Kristen membawa siswa untuk semakin mengenal Tuhan, mengembangkan potensi setiap peserta didik sesuai dengan kebenaran dan maksud Tuhan. Pembelajaran matematika seharusnya menjadi alat untuk membawa siswa semakin melihat dan mengagumi Allah sebagai Pencipta yang agung. Melalui investigasi dan penemuan dalam belajar matematika seharusnya menjadi pengakuan dari beberapa atribut Allah yang membawa siswa untuk mengagumi keindahan matematika dan membawa siswa untuk memuji Tuhan.